O avtobiografiji z vidika sodobne genologije in sistemske teorije - Leben, Andrej (Primerjalna književnost, 2007)
This article discusses the character of the genre of autobiography against a background of traditional views on literary genres, and post-structuralist and culturological models. From the viewpoint of empirical and systematic discussion of literature, it seeks to demonstrate that autobiography could play an important role in current efforts to reform literary studies in dialogue with other disciplines.
Keywords: literarne zvrsti; literarni žanri; autobiography; avtobiografija; genologija; sistemska teorija